High-resolution direct printing of molten-metal using electrohydrodynamic jet plotting. (April 2017) - Han, Yiwei; Dong, Jingyan
Abstract: In this paper, a high-resolution direct printing process was developed for molten metal using Electrohydrodynamic (EHD) printing technology. The effect of the critical printing conditions, such as voltage and printing speed, on the printing process was characterized. Compared with direct extrusion using pneumatic pressure, the EHD printing can effectively reduce the dimension of the printed filament down to less than 50 μm with better quality of the printed features. We successfully applied EHD printing to print high-resolution 2D patterns and some high aspect-to-ratio 3D structures, which demonstrated the potential capabilities of EHD printing process in producing fine metal structures.